Hi tech microeconomics and information non-intensive calculi - Dohnal, Mirko; Kocmanova, Alena; Rašková, Hana (Vysoké učení technické v Brně, Fakulta podnikatelská, 2008)
The article establishes link between the contributions made to the study of hi tech phenomena. It analyzes the evolution undergone by studies on the topic of the knowledge economics (HI-TECH) process carried out by different disciplines (hard and soft sciences – sociology, ecology etc.) from the point of view of the objectives they pursue. The attentions are concentrated on analysis of applicable mathematical tools used to develop realistic formal models. Information intensity is defined as the amount of information which is needed for the realistic application of a corresponding formal tool. High information intensity is desirable because it influences the model accuracy. Low information intensity is preferred when high information intensity requires more information items than are available and this is usually the case in knowledge engineering. Fuzzy models seem to be a useful extension of formal tool used in hi tech microeconomics. However, even fuzzy sets could be prohibitively information intensive. Therefore the range of available formal tools must be considerably broader. This paper introduces qualitative and semiqualitative models and rough sets. Each formal tool is briefly characterized.
Keywords: Hi tech; Fuzzy; Rough; Non-intensive calculi; Microeconomics